A market for work permits. (11th February 2022) - Lokshin, Michael; Ravallion, Martin
Abstract: It will be politically difficult to liberalize international economic migration without some form of compensation for host-country workers. The paper explores the scope for managing migration using a government-regulated competitive market for work permits (WPs). We propose that host-county workers should be granted the legal option of renting out their WPs for a period of their choice, while foreigners can purchase taxable time-bound WPs. The proposed market is anonymous, with no need for personalized matchings of those on its two sides. The market can have either one price or be differentiated by occupation or region. There would probably be some losers, but potentially large gains, including through enhanced social protection in host countries. Using its power to tax WPs, the host country can achieve any desired floor to labour earnings. The market for WPs can also provide a new instrument for implementing industrial and regional development policies.